2021
DOI: 10.2147/prbm.s305979
|View full text |Cite
|
Sign up to set email alerts
|

Risky Decision-Making and Hazard Prediction are Negatively Related and Could Be Assessed Independently Using Driving Footage

Abstract: Introduction: Traffic collisions are a principal cause of death in Europe, disproportionately affecting young drivers. Driving safety depends not only on our ability to anticipate and respond to dangers on the road but also on the level of risk we are willing to engage within our own driving behaviour. Methods: Hazard prediction (HPr) and risky decision-making (RDM) tests were given to three groups of young Spaniards (169 participants): 54 non-drivers (M=20), 65 novice (M=21) and, 50 experienced drivers (M=26 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…While participants in online studies are susceptible to distraction and often multitask, studies have reported that they are still capable of providing conscientious and thoughtful answers independently of the device or context [ 127 , 128 ]. In addition, this online version of the study has replicated the results obtained by Castro et al [ 101 ], who conducted their study in laboratory settings. These results indicate that online assessment could be a plausible option for future research.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…While participants in online studies are susceptible to distraction and often multitask, studies have reported that they are still capable of providing conscientious and thoughtful answers independently of the device or context [ 127 , 128 ]. In addition, this online version of the study has replicated the results obtained by Castro et al [ 101 ], who conducted their study in laboratory settings. These results indicate that online assessment could be a plausible option for future research.…”
Section: Discussionsupporting
confidence: 83%
“…Second, experience is often associated with hazard perception (driving skill), which is independent of the willingness to engage in risky driving behaviour [ 28 , 38 , 70 ]. Castro et al [ 101 ] emphasised the importance of assessing hazard perception (driving skill) and risky decision making (willingness to engage in risky driving) separately to avoid confounding both variables. This is of importance, as drivers could correctly perceive a hazard and at the same time underestimate the danger this hazard poses [ 111 , 112 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations